Gender Equality in Batak Toba Wedding Ceremony - Sitinjak, Vivi Novalia; Ginting, Wina Ecica br; Tumanggor, Tri Fazar; Hasibuan, Nobel (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2023)
Batak Toba is one of the tribes in North Sumatra. In Batak custom where men buy women in marriage. The position of men is higher in the Batak tribe because it follows the patriarchal lineage where men are the successors of the descendants or clans. In general, women do not have an important position or position in every traditional event that is carried out. Because men take all the important roles in every traditional Batak Toba event. In this analysis, because of gender is an interesting thing to discuss, especially in Batak Toba ceremony. This article use Liberal and Radical Feminism (in Tong, 2006). The objective of this research is to promote fairness and balance in the roles and responsibilities of men and women during the event is the goal of gender equality in Toba Batak wedding ceremonies. This attempts to guarantee that both partners actively participate in and enjoy the ceremony on an equal footing, and that traditions and customs do not perpetuate gender-based discrimination. Therefore, it is important to apply justice which refers to gender equality in the Batak Toba tribe. With the passage of time, it is hoped that this tradition will continue to empower women to be able to communicate with elders.